GIS-Based Analysis of Vegetation Density and Green Open Space Utilization at UNTAG Samarinda - Andrew Stefano; Sri Endayani; Djumansi Derita (P3KM Politeknik Pertanian Negeri Samarinda, 2025)
The Universitas 17 Agustus 1945 (UNTAG) Samarinda is one of the educational institutions located in urban areas with high development pressure. The existence of green open spaces in the campus environment plays an important role in maintaining ecological balance, thermal comfort, and air quality for the academic community. This study aims to evaluate the level of vegetation density and proportion of green open space utilization in the UNTAG Samarinda campus area using the Geographic Information System (GIS) approach. Spatial data was obtained from high-resolution satellite imagery in 2024 and field interpretation results that included tree vegetation, shrubs, and non-green areas (buildings and roads). Data processing is carried out through the stages of geometric correction, land cover classification, and vegetation index analysis (NDVI). The results of the analysis showed that of the total land area ±2.98 hectares, around 32.6% is a vegetation area with a medium-high density level, while the rest is in the form of buildings, parking areas, and road access. These findings show the need for a more optimal Green Open Space management strategy through increasing vertical vegetation and greening in the open areas of the campus. GIS integration has proven to be effective in providing accurate spatial information to support sustainable campus planning and support UNTAG Samarinda's